Kepercayaan Merek Dari Testimoni Jamaah Sebagai Benteng Reputasi KBIHU Yamisa Pasca Krisis Haji 2025 - Diyah Anggraeni Rimayansyah; Ahmad Taufiq Maulana Ramdan (Komunika : Jurnal Ilmiah Komunikasi, 2025)
This study aims to analyze how KBIH Yamisa maintains and restores its reputation amid the 2025 national hajj quota corruption crisis that triggered a significant decline in public trust toward hajj management institutions in Indonesia. Using a qualitative approach through in-depth interviews, observations, and documentation, the study reveals that KBIH Yamisa’s brand trust remains strong due to consistent service delivery, transparent communication, and solid interpersonal relations between the institution and its pilgrims. The findings highlight that pilgrims’ direct experiences and organically spread testimonials significantly influence public perceptions and help sustain institutional credibility. These results align with the Relationship Management Theory, which emphasizes two-way communication, commitment, and trust as essential components of durable organization–public relationships. The study concludes that brand trust and pilgrims’ testimonials serve as effective Public Relations strategies for maintaining the reputation of religious institutions during external crises